1979
DOI: 10.1084/jem.149.6.1438
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of an extracellular blastogen produced by group A streptococci.

Abstract: An extracellular product of group A streptococci which induces lymphocyte blastogenesis has been purified to homogeneity by DEAE-cellulose and CM-cellulose chromatography. The protein, termed streptococcal blastogen A, has a mol wt of approximately or equal to 17,500 and is inactivated by protease treatment and by heating at 100 degrees C. The purified blastogen gave rise to multiple protein bands on nondenaturing polyacrylamide gel electrophoresis, only two of which possessed blastogenic activity. Treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Their products have been studied extensively [1,2]. A substance which they produce, the streptococcal mitogen (SM), stimulates both B and T cells [3]; induces Ia antigens on purified T lymphocytes [3]; and at a low concentration can distinguish normal lymphocytes from those of subjects with a history of RF [34].…”
Section: Introductionmentioning
confidence: 99%
“…Their products have been studied extensively [1,2]. A substance which they produce, the streptococcal mitogen (SM), stimulates both B and T cells [3]; induces Ia antigens on purified T lymphocytes [3]; and at a low concentration can distinguish normal lymphocytes from those of subjects with a history of RF [34].…”
Section: Introductionmentioning
confidence: 99%
“…containing 100 U/ml of penicillin, 100 ug/ml streptomycin, 50 ,g/ml of gentamycin, and 2 mmol/ml L-glutamine (MEM-PSG). The cell suspension was fractionated by centrifugation on a Ficoll-Hypaque gradient as previously described (15). The samples of blood were diluted with an equal volume of MEM-PSG and the monocyte population isolated in the same manner.…”
Section: Methodsmentioning
confidence: 99%
“…Streptococcal blastogen A and streptococcal nuclease B were purified from the crude extracellular products ofgroup A streptococcal strain C203S3 as previously described (15 blood agar plates. After overnight incubation at 370C, the streptococcal colonies were categorized as a-or f8-hemolytic and colonies exhibiting f8-hemolysis were isolated and serologically grouped (19).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Group A streptococci express a large number of extracellular factors that may contribute to pathogenicity. Among these are several nonspecific lymphocyte mitogens, and at least two of these have been shown to stimulate T-cell proliferation while not inducing B-cell division (1,6). Barsumian et al (1) and others (14) showed that streptococcal pyrogenic exotoxins (SPEs, also known as scarlet fever toxins and erythrogenic toxins) of types A, B, and C nonspecifically induce proliferation of rabbit splenocytes and human T cells while not stimulating murine spleen cells.…”
mentioning
confidence: 99%